2022
DOI: 10.1038/s12276-022-00760-w
|View full text |Cite
|
Sign up to set email alerts
|

An aptamer agonist of the insulin receptor acts as a positive or negative allosteric modulator, depending on its concentration

Abstract: Aptamers are widely used as binders that interact with targets with high affinity or as inhibitors of the function of target molecules. However, they have also been used to modulate target protein function, which they achieve by activating the target or stabilizing its conformation. Here, we report a unique aptamer modulator of the insulin receptor (IR), IR-A62. Alone, IR-A62 acts as a biased agonist that preferentially induces Y1150 monophosphorylation of IR. However, when administered alongside insulin, IR-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The A62 aptamer not only acts as an agonist, but also positively regulates the binding of insulin to IR at low concentrations 18 . The structure of the IR A62+Ins complex is asymmetric, with one insulin and one A62 bound at each site of the dimer (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The A62 aptamer not only acts as an agonist, but also positively regulates the binding of insulin to IR at low concentrations 18 . The structure of the IR A62+Ins complex is asymmetric, with one insulin and one A62 bound at each site of the dimer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These ligands include antibodies, peptides, and nucleotides that selectively activate the AKT pathway and induce metabolic effects, but exert much weaker MAPK pathway signaling and mitogenic effects than insulin 13 17 . Moreover, some IR agonists also lead to site-specific mono-phosphorylation of Tyr1150 (m-pY1150) in the kinase domain of IR 17 , 18 . Thus, studies of these agonists of suggest that the early IR intermediates with site-specific Tyr phosphorylation in the activation event are responsible for the selective stimulation of the metabolic signaling 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can specifically and strongly bind to the target with high affinity due to their unique 3D structures [ 151 ]. Studies have reported on various aptamers ( Table 2 ), such as IR-A48 [ 152 ], IR-A43 [ 153 ], IR-A62 [ 154 ], and GL56 [ 155 ]. IR-A48 is an agonistic aptamer that binds to and then activates the IR [ 152 ].…”
Section: Pharmacological and Physiological Modulators Of Ir Activationmentioning
confidence: 99%
“…IR-A43 is a sensitizing aptamer that effectively binds to the IR and enhances insulin sensitivity [ 153 , 156 ]. IR-A62 acts as a biased agonist that binds to the extracellular domain of the IR and preferentially induces Y1150 monophosphorylation of IR [ 154 ].…”
Section: Pharmacological and Physiological Modulators Of Ir Activationmentioning
confidence: 99%